A poem (A Message on the Night of Execution) by Hashem Al-Rifai, a critical psychological study - Ihsan Burhanuldeen Ameen (Zanco Journal of Humanity Sciences)
For the poet Hashem Al-RifaiThis research deals with the analysis of the poem "A Message on the Night of Execution" by the Egyptian poet Hashem Al-Rifai according to the psychological method. From the human feelings and the raging emotions emanating from the situation that was depicted, which made it worthy of correcting the lights of study on it from a psychological point of view, and it was discussed before that about the poet’s life from his birth to his death, as well as highlighting the poem in terms of presentation to show the extent of harmony The poetic sea with the content addressed by the poet.